Comparison of nasal senses following open and closed rhinoplasty - Okur, Mehmet Ihsan; Gokdemir, Onur; Karasu, Necmettin; Yildirim, Alpagan Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2016)
Background/aim: The objective of this study was to compare the postoperative changes taking place in the nasal senses of patients who underwent a rhinoplasty through the open or closed incision method. Materials and methods: In a prospective study, 15 patients had a closed rhinoplasty surgery and 15 others had an open one. By pinpointing 9 spots in the nose, a sensory assessment was made by means of Semmes-Weinstein monofilaments prior to the surgery and 1 week and 1, 3, and 6 months after the surgery. Results: In the open and closed groups, there was hypoesthesia 1 week after the surgery compared with the preoperative period (P = 0.01 and P = 0.016). In the first week a sense reduction in the upper columella was observed in the open group when compared with the closed one (P = 0.035). There were no other significant differences between the groups in the nasal regions at other times. Conclusion: It was ascertained that there was reduced sensation in the upper columella in the open incision group in the first postoperative week. The sensation was reduced in both groups in the first postoperative week. The nasal sensation recovered after the first month.
Keywords: Rhinoplasty; septorhinoplasty; nasal sense; open rhinoplasty; closed rhinoplasty